Toward a New Era in Physical Education (Fiep Bulletin - online, 2015)
Revolutionary changes are taking place in twentietn century school life, the global impact and repercussions of which seem to have farreaching effects upon the development of contemporary physical education in its manifold manifestations ( gymnastics, games, sports, hygiene).